Pengaruh atraksi, aksesibilitas dan amenitas terhadap minat kunjungan wisatawan ke kawasan ekonomi khusus (KEK) pariwisata Tanjung Lesung Banten - Saepullah, Asep; Himawan, Andre (Journal of Economic Resilience and Sustainable Development, 2024)
This research aims to determine the interest of tourists in visiting the particular economic area in the Tanjung Lesung Banten Tourism area. By being designated as a particular economic group, tourist interest should increase along with improvements in facilities and infrastructure in Banten. This research uses a quantitative approach with survey methods. The sample of respondents was 85, with processed data from 73 respondents who had visited Tanjung Lesung Beach Resort and Tanjung Lesung Beach Club, selected using a purposive sampling technique. Data analysis was carried out in stages using validity and reliability tests. The data was transformed using the MSI method into interval data and then analyzed using Multiple Regression Analysis. The results show that attractions have the highest and most significant value on tourist interest in visiting Tanjung Lesung. On the other hand, accessibility and amenities individually do not significantly affect tourists' interest in visiting.